DETERMINATION OF RISK PREMIUM USING CREDIBILITY THEORY BASED ON UNCERTAINTY - ANGGRAENI (NIM : 20813002); Pembimbing : Dumaria R. Tampubolon, Ph.D, SILVY
The prediction of the risk premium depends on three sources of uncertainties: model uncertainty, parameter uncertainty, and the uncertainty of the process generating the data. In this thesis, the parameter uncertainty is considered to predict the risk premium of a client. Having not enough or having problems in the historical claims data of a client may contribute to the parameter uncertainty. Hence, to overcome this problem, information from the market is used. In this thesis, a methodology to predict the risk premium of a client using credibility theory based on the uncertainty of the risk premium is discussed. The methodology make use the uncertainty of the client risk premium, the uncertainty of the market risk premium, and the correlation between them. In this methodology, the client is part of the market. The claims data analyzed in this thesis is generated by Monte Carlo simulation. The inclusion of the information from the market have an effect on the uncertainty of the parameter which in turn affecting the prediction of the risk premium of the client.